Assessing the visibility and public engagement of bone marrow and stem cell transplantation research: An altmetric analysis - Mohammad Ahmadian; Shaban Alizadeh; Azadeh Omidkhoda; Fatemeh Sheikhshoaei; Brenda Van Wyk (Heliyon)
Background: Bone marrow and stem cell transplantation have led to significant advancements in modern medicine, offering potential cures for various hematological disorders and specific cancers. This study aims to investigate and analyze research in this field using altmetrics in a world outside the academic scholarly and publishing environment. Methods: This study examines articles in the field of bone marrow and stem cell transplantation in a ten-year period (2013–2022) extracted from the Web of Science database. The Altmetric Explorer database and tool were used to extract data. After an initial review of the data for their completeness and accuracy, the study considered descriptive reports, statistical analyses, bibliometric network analysis, and overlaps between articles, journals, and research centers in terms of the Altmetric Attention Score (AAS) and citations using Excel, SPSS, Python, R, and VOSviewer. Result: This study evaluated 12924 articles published in 293 journals. Findings show that 85.67% of the articles were mentioned at least once on various social media and their tools. The AAS varied between 0 and 1125, and the median of this score was 2. The highest score was assigned to an article that provides critical insights into the outcomes of patients with refractory diffuse large B-cell lymphoma (DLBCL). Mendeley, X (formerly Twitter), and News were the most important and active social tools, respectively, where these articles were mentioned. The highest number of tweets, news stories, Facebook posts, and policy documents were from the USA, USA, USA, and UK, respectively. The @PaperbirdsM and @MayoClinic accounts on X had the highest tweet and follower statistics, respectively. The University of Texas MD Anderson Cancer Center also had the highest number of mentions on social networks. Network analysis maps of the top AAS articles showed “Stem Cell Transplantation” as the most popular author keyword, with Blood having the most influence at the journal level, the USA at the country level, Memorial Sloan Kettering Cancer Center at the research center level, and Kenneth C. Anderson at the author level. Finally, the results of the tests showed a significant correlation between citation and Altmetric indicators/AAS. However, nor were there differences in AAS based on the open access status of articles or the journal quartile. Conclusion: A high percentage of articles in this field are present on social networks and platforms. Furthermore, highly cited articles on social media have attracted more attention. Both traditional and web-based metrics offer different perspectives on scholarly impact. While each provides valuable insights, further research is needed to explore how these metrics can be effectively combined for a more comprehensive evaluation of scientific outputs.